SISTEMPENDUKUNG KEPUTUSANMENENTUKAN MAHASIWA LULUSAN TERBAIK DI FAKULTAS ILMU-ILMU SOSIAL UNIVERSITAS DEHASEN BENGKULUMENGGUNAKAN METODE AHP - Rimba Putri Yani; Asnawai Asnawati; Feri Hari Utami (Jurnal Media Infotama, 2023)
Abstract: Decision Support System for Determining the Best Student in the Faculty of Social Sciences, University of Dehasen Bengkulu Using the "Analytical Hierarchy (AHP) Method" The ability to make quick and careful decisions will be the key to success in global competition in the future. Having a lot of information alone will not be enough, if you are able to mix it quickly into the best alternatives for decision making, to help humans, especially decision makers in determining virtues, in a precise, efficient and effective manner, a decision-making model known as the System is needed. Decision Support (SPK). Data processing aids accompanied by software can increase the ability of decision makers, improve accuracy and speed up the process. From the design process to the implementation of the system that has been carried out in the Decision Support System for Determining Outstanding Students at the Faculty of Social Sciences, Dehasen University, Bengkulu Using the Analytical Hierarchy (AHP) method, several conclusions can be drawn as follows: Decision Support System for Determining Outstanding Students at the Faculty of Social Sciences, University of Dehasen Bengkulu Using the Analytical Hierarchy Method (AHP is a website application that can be accessed flexibly by both users and admins/campus parties, only with an internet connection. This system can already be used to provide detailed purchase transaction reports, sales reports and product reports. Keywords, AHP, SPK, Mysql & PHP